2021
DOI: 10.3329/ajmbr.v7i2.54987
|View full text |Cite
|
Sign up to set email alerts
|

Research trends of aqua medicines, drugs and chemicals (AMDC) in Bangladesh: the last decade's (2011-2020) story to tell

Abstract: Aquaculture medicines, drugs, and chemicals or simply AMDC, are critical in protecting aquaculture farmers from disease in farmed animals and economic losses. The AMDC is now a well-established industry in Bangladesh, and each year, new products that benefit farmers are launched. This review examined published research information on AMDC over the last decade (2011-2020) and discovered that 41 research publications from various parts of Bangladesh were published, citing the names of 1484 AMDC products. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…We found a total of 30 brands of antibiotics were reported from the study area. A total of 58 antibiotics have been recorded from various parts of Bangladesh previously (Asif et al, 2021). Lulijwa et al (2020) studied antibiotic usage in key aquaculture-producing countries, including Bangladesh, and found that 19 antibiotics are used in Bangladeshi aquaculture.…”
Section: Antimicrobial Resistance (Amr) In Aquaculturementioning
confidence: 99%
See 1 more Smart Citation
“…We found a total of 30 brands of antibiotics were reported from the study area. A total of 58 antibiotics have been recorded from various parts of Bangladesh previously (Asif et al, 2021). Lulijwa et al (2020) studied antibiotic usage in key aquaculture-producing countries, including Bangladesh, and found that 19 antibiotics are used in Bangladeshi aquaculture.…”
Section: Antimicrobial Resistance (Amr) In Aquaculturementioning
confidence: 99%
“…Due to a lack of vaccination and good health management practices, disease problems in Bangladesh's aquaculture business remain unresolved. Experts advised that the fish vaccinations for disease resistance prevent death and economic loss (Assefa and Abunna, 2018), but in this region, this vaccination initiative needs a massive process, infrastructure, funding, and timeline (Asif et al, 2021). To combat fish diseases, farmers apply a variety of chemicals and medicines.…”
Section: Introductionmentioning
confidence: 99%
“…58 Earlier study reported the use of 530 g of antibiotics per tonne of salmon harvested during 2016; Florfenicol (82.5%) and OTC (16.8%) were the most frequently used antibiotics. 59 In order to address the issue of AMR due to use of antibiotics in food animal pro- Canada, [59][60][61][62] in Asian 20 and European aquaculture, 63 Bangladesh 16 and the global trend in use of antibiotics in aquaculture. 17,36…”
Section: Determinants Of Chemical Usementioning
confidence: 99%
“…Generally, chemicals, nutritional supplements, probiotics, disinfectants, antimicrobials and antiparasitic agents are applied in aquaculture operations to maintain optimal environmental quality, improved health, growth, production and protection against microbial and parasitic diseases. Though the contribution of these interventions in achieving the higher production and economic sustainability of the sector is not questioned, concerns have been raised about their possible environmental accumulation and presence of residues in the edible tissue 7–19 . Non‐judicious use of disinfectants and antiparasitic agents might affect the non‐target organisms leading to potential ecological degradation 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation